PENGARUH PROMOSI DAN KUALITAS PELAYANAN TERHADAP KEPUASAN NASABAH DALAM PEMAKAIAN JASA KREDIT PADA PERUM PEGADAIAN - Ratiyah, - (Perspektif : Jurnal Ekonomi dan Manajemen Akademi Bina Sarana Informatika, 2015)
ABSTRACT Perum Pegadaian is a non-bank financial institutions that provide credit services to the public. For that good service is the top priority so that the satisfaction of the public or customers can be achieved. To improve customer satisfaction Pawnshop improve service quality and innovation promotion strategy so that customers interested decided to use the services of credit Pawnshop. The level of customer satisfaction is influenced by several factors such as the promotion and quality of service. Therefore, this study was conducted to analyze how much influence the promotion and service quality to customer satisfaction in the use of credit services. This research was conducted in Housing pawnshops East Jakarta branch milling. By using quantitative analysis of correlation and linear regression, where the promotion of its independent variables (x1) and quality of service (x2) and customer satisfaction dependentnya variable (y). In this study, the authors take 10% of the population to be sampled or sampling Saturated known by as many as 83 people. Sample size determination based on a model developed by Isaac and Michael in Sugiyono (2008) to calculate the error rate, 1%, 5%, 10%. The data obtained from the questionnaire were given a score of a predetermined value and statistically analyzed using Statistical Computer Program Product for service solution (SPSS) 19 for windows. Based on this study it can be concluded that there is significant influence promotion and service quality on customer satisfaction in the use of credit services in Perum PegadaianKeywords: Promotion, Quality of Service and Customer Satisfaction